Polymorphism 2184A/G in the AGER gene is not associated with diabetic retinopathy in Han Chinese patients with type 2 diabetes. (June 2016) - Li, Jian; Cai, Wei; Zhang, Wei; Zhu, Wei-Feng; Liu, Ying; Yue, Li-Xia; Zhu, Ling-Yan; Xiao, Jun-Ren; Liu, Jian-Ying; Xu, Ji-Xiong
Objective: To assess the association between the 2184A/G polymorphism in the advanced glycosylation end product-specific receptor ( AGER ) gene and the susceptibility to diabetic retinopathy (DR) in Han Chinese patients with type 2 diabetes mellitus (T2DM). Methods: This cross-sectional genotyping study included patients with T2DM with and without DR. Genotype and allele frequencies of the 2184A/G polymorphism were detected using polymerase chain reaction–restriction fragment-length polymorphism analysis. Results: This study included 943 patients with T2DM (285 with DR [DR group] and 658 without DR [NDR group]). There were no significant differences in age, sex, body mass index, total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, diastolic blood pressure, glycosylated haemoglobin, fasting blood glucose, postprandial 2-hour blood glucose, and triglycerides between the two groups. The duration of T2DM and systolic blood pressure were significantly increased in the DR group compared with the NDR group. No significant differences were found in allele (A and G) and genotype (AA, AG and GG) frequencies of the 2184A/G polymorphism between the two groups. Conclusion: The 2184A/G polymorphism in the AGER gene is not associated with DR in Han Chinese patients with T2DM.